Information resources distribution between automated workstations in local corporative networks - Pursky, O.I.; Kozlov, V.V.; Tomashevska, T.V.; Dyvak, V.V.; Hordiiko, N.O.; Sinitsky, M.Y. (Проблеми програмування, 2022)
This article focuses on the problem of optimal distribution of related information resources between automated workstations in local corporate networks. In this work we present a mathematical description of the algorithm for quasi-optimal distribution of related information resources at designing automated workstations in a local corporate network. The undirected graph describing the task of information resources optimal distribution is presented. The method of quasi-optimal distribution of related resources at designing automated workstations in the local corporative network is proposed based on the developed algorithm. Using conditional organization as an example the modeling of optimal distribution of related information resources has been considered in local corporative network. The described algorithm provides an opportunity to optimally distribute the information resource in the local corporate network, as well as solve the task of building reliable and efficient local networks. The proposed method of quasi-optimal distribution of related information resources can be used in corporation of any type.